PARTISIPASI MASYARAKAT MEMODERASI HUBUNGAN TRANSPARANSI DAN AKUNTABILITAS TERHADAP PENGELOLAAN DANA DESA DAN PEMBANGUNAN INFRASTRUKTUR - Rohmah, Siti; Robert, Martinus; P. Pardede, Pantas; Yunan, Nadiya; Siang, Diana; Humairah, Rika (Jurnal GeoEkonomi, 2025)
This research aims to test how much influence Transparency and Accountability have on Village Fund Management moderated by Community Participation. The method in this research is to use quantitative methods and saturated sampling methods as a method for selecting a sample of 130 respondents. The data collection technique uses a questionnaire which is measured using a Likert scale. The data analysis technique used is Multiple Linear Regression Analysis using the SPSS program. The research results show that Transparency and Accountability have a positive and significant effect on Village Fund Management. Thus, Community Participation - Transparency has a significant effect on Fund Management, while Accountability is not influenced, meaning that Community Participation cannot moderate the influence of accountability on fund management. Apart from that, village fund management has a significant effect on infrastructure development.